The Role of Agricultural Extension Workers in Capacity Development Member of the Rice Farmers Group in Panca Rijang District - Nurul Fitriyah; Iranita Haryono; Ayu Wulandary (Agribusiness Journal, 2024)
Agricultural instructors in Panca Rijang District need to become facilitators, innovators, motivators, dynamists and educators if they want to increase rice production and farmers' abilities. This research aims to find out how the ability of rice farmers in Panca Rijang District is influenced by the role of agricultural instructors. The methodology of this research is quantitative descriptive. Primary data and secondary data are used. The Random SampIing SimplIe is used for the sample collection process, and the SIovin formula is used to determine the sample size. Questionnaires were used to interview 44 farmers in total. The analysis technique used is multiple linear regression. Research findings show that the role of agricultural instructors as facilitators, innovators, motivators, dynamists and educators has a significant influence on developing the abilities of farmer group members in Panca Rijang District as evidenced by a significant value of 0.000 0.05 and a calculated F value of 13.486 F table 2 .46.